Shallow Bounding Volume Hierarchies for Fast SIMD Ray Tracing of Incoherent Rays - Dammertz, H.; Hanika, J.; Keller, A. (Computer graphics forum, 2008)
Photorealistic image synthesis is a computationally demanding task that relies on ray tracing for the evaluation of integrals. Rendering time is dominated by tracing long paths that are very incoherent by construction. We therefore investigate the use of SIMD instructions to accelerate incoherent rays. SIMD is used in the hierarchy construction, the tree traversal and the leaf intersection. This is achieved by increasing the arity of acceleration structures, which also reduces memory requirements. We show that the resulting hierarchies can be built quickly and are smaller than acceleration structures known so far while at the same time outperforming them for incoherent rays. Our new acceleration structure speeds up ray tracing by a factor of 1.6 to 2.0 compared to a highly optimized bounding interval hierarchy implementation, and 1.3 to 1.6 compared to an efficient kd‐tree. At the same time, the memory requirements are reduced by 10–50%. Additionally we show how a caching mechanism in conjunction with this memory efficient hierarchy can be used to speed up shadow rays in a global illumination algorithm without increasing the memory footprint. This optimization decreased the number of traversal steps up to 50%.